2018
DOI: 10.1111/1759-7714.12903
|View full text |Cite
|
Sign up to set email alerts
|

MiR‐145‐targeted HBXIP modulates human breast cancer cell proliferation

Abstract: BackgroundMiR‐145 has been identified as a tumor suppressive microRNA in multiple cancers. In this current investigation, we searched for new direct targets of miR‐145 and evaluated their effect on breast cancer development.MethodsTargetscan was used to predict the target genes of miR‐145. The targeting of miR‐145 on oncogenic HBXIP was verified by luciferase reporter gene analysis. The effect of miR‐145 on the level of messenger RNA and protein of HBXIP was evaluated by quantitative real‐time PCR and immunobl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 29 publications
0
14
0
1
Order By: Relevance
“…Up to now, miRNAs have been revealed that they are involved in a large amount of biological processes, including tumour formation and inflammatory responses in many human diseases [25][26][27]. It is well known that miR-199a-5p has been studied to take part in the progress of cancer [28].…”
Section: Discussionmentioning
confidence: 99%
“…Up to now, miRNAs have been revealed that they are involved in a large amount of biological processes, including tumour formation and inflammatory responses in many human diseases [25][26][27]. It is well known that miR-199a-5p has been studied to take part in the progress of cancer [28].…”
Section: Discussionmentioning
confidence: 99%
“…To date, miRNAs have been reported to be implicated into some biological processes, including tumorigenesis and inflammatory response in numerous human diseases 1517. As known to all, miR-145 has been reported to exert different effects on the development and progression of cancers.…”
Section: Discussionmentioning
confidence: 99%
“…MiRNAs have been demonstrated to be involved in various human diseases, and play important roles in cellular differentiation, proliferation, metastasis and EMT 12. Notably, aberrant miR-145 expression was also reported to be implicated in cancer progression by regulating target genes 1315. Using bioinformatics analysis, we found that Smad2 was also a potential candidate target of miR-145.…”
Section: Introductionmentioning
confidence: 87%
“…Götte et al, 2010 also demonstrated that miR-145 modulates the actin cytoskeleton remodeling and homogenizes cortical actin distribution, nuclear rotation, and migration via the direct interaction with 3′UTR of JAM-A and fascin in MDA-MB-231 cells [ 154 ]. In a similar context, the expression of SMAD3 [ 148 ], DR5 [ 148 ], BRCA2 [ 148 ], HBXIP [ 155 ] and RTKN [ 156 ] directly silenced by miR-145 inhibits tumor metastasis. Angiogenesis is one of the hallmarks of epithelial–mesenchymal transition (EMT).…”
Section: Roles Of Mirnas In Cancermentioning
confidence: 99%